THE EFFECTIVENESS OF DELAYED CORD CLAMPING ON INFANT OUTCOMES - Amalia, Rizki; Fathony, Zaiyidah; Lestari, Pratiwi Puji (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Introduction: Lately, delayed cord clamping is often used as a method of cutting the umbilical cord which is expected to provide good outcomes for the baby, but this method still needs to be studied in depth through review articles to find out its effect. This study aims to compare the results of studies on the effectiveness of delayed cord clamping methods on bilirubin levels and neurodevelopment of infants and toddlers.Method: The method in this study is a scoping review with PRISMA guidelines, the data bases used are Pubmed and Google Schoolar. The inclusion criteria for this study included randomized control trial, quasi-experimental, and clinical trial designs.Result: There are 6 articles that discuss the effectiveness of DCC on neurodevelopment. In the Age of stage questionnaire, there are 5 domains that have high average values, which are problem solving, fine motor skills, and communication. On the Bayley Scales of Infant Development questionnaire which has the highest average score is the motor cognitive domain. Most of the articles that discuss the effectiveness of DCC on bilirubin levels show that there is an increase in bilirubin levels after the DCC intervention.Conclusion: DCC is less effective on neurodevelopment and bilirubin levels. It is necessary to develop further research in Indonesia regarding the effects of DCC on neurodevelopment and bilirubin levels